2008
DOI: 10.4238/vol7-4gmr497
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism in adult soft tissue sarcomas

Abstract: AbSTRACT. Soft tissue sarcomas (STS) are tumors of mesodermal origin, comprising about 1% of all adult neoplasms. Management of such tumors is an important medical challenge. TP53 codon 72 polymorphism results in either the arginine or proline form of the p53 protein; several studies have investigated whether codon 72 polymorphisms are risk and prognostic factors for cancer. We investigated p53 codon 72 polymorphism (Arg72Pro) frequencies with respect to the susceptibility and the clinical outcome of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Of these 29 studies, 25 studies were excluded either because they were not case-control studies or they are not studies on sarcomas or reports on the role of P53 Arg72Pro on patient survival or disease progression. Among these four case-control studies, Savage et al (2007) and Toffoli et al (2009) investigated role of P53 Arg72Pro in osteosarcoma development among Caucasians, and the other two studies examined effects of this SNP on carcinogenesis of soft tissue sarcomas or Kaposi's sarcoma in mixed populations (Almeida et al 2008;Tornesello et al 2009). In addition, after searching HuGE Navigator and NCBI PubMed using the keywords ''MDM2,'' ''HDM2,'' ''sarcoma,'' ''polymorphism,'' or ''SNP,'' we found 13 studies.…”
Section: Literature Search and Data Extractionmentioning
confidence: 98%
“…Of these 29 studies, 25 studies were excluded either because they were not case-control studies or they are not studies on sarcomas or reports on the role of P53 Arg72Pro on patient survival or disease progression. Among these four case-control studies, Savage et al (2007) and Toffoli et al (2009) investigated role of P53 Arg72Pro in osteosarcoma development among Caucasians, and the other two studies examined effects of this SNP on carcinogenesis of soft tissue sarcomas or Kaposi's sarcoma in mixed populations (Almeida et al 2008;Tornesello et al 2009). In addition, after searching HuGE Navigator and NCBI PubMed using the keywords ''MDM2,'' ''HDM2,'' ''sarcoma,'' ''polymorphism,'' or ''SNP,'' we found 13 studies.…”
Section: Literature Search and Data Extractionmentioning
confidence: 98%
“…Codon 72 polymorphism on the 4th exon of TP53 is involved in multiple steps of carcinogenesis and may also account for genetic differences in susceptibility to cancer (Boltze et al, 2002;Aral et al, 2007;Almeida et al, 2008). It has been demonstrated that the TP53 polymorphism varies according to ethnic and geographical distribution, like most human genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…The most common polymorphism at codon 72 results in a nonconservative change of arginine to proline within a proline-rich region of p53, in a domain known to be important for growth suppression and apoptotic functions (Tornesello et al, 2008), may be involved in multiple steps of carcinogenesis and may also account for genetic differences in susceptibility to cancer (Reis et al, 2010b;Tornesello et al, 2008, Almeida et al, 2008. It has been demonstrated that the TP53 polymorphism distribution varies according to ethnic and geographical backgrounds, like most human genetic polymorphisms (Reis et al, 2010b).…”
Section: Effect On the Sperm Parametersmentioning
confidence: 99%